OUTCOME OF LONG SEGMENTAL RECONSTRUCTION (LSR), OF THE LEFT ANTERIOR DESCENDING ARTERY (LAD) WITH THE LEFT INTERNAL MAMMARY ARTERY (LIMA), IN PATIENTS UNDERGOING CORONARY ARTERY BYPASS GRAFT (CABG) SURGERY FOR DIFFUSE CORONARY ARTERY DISEASE (CAD) - Zamir, Ali Gohar; Pervaiz, Farrah; Iqbal, Mishal; Malik, Waqar Masud; Malik, Faiq Ahmed; Malik, M. Afsheen (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine the outcome of long segmental reconstruction (LSR), of the Left Anterior Descending Artery (LAD) with the Left Internal Mammary Artery (LIMA), in patients undergoing Coronary Artery Bypass Graft (CABG) surgery for diffuse Coronary Artery Disease (CAD) affecting the LAD. Study Design: Descriptive cross-sectional study. Place and Duration of Study: Department of Adult Cardiac Surgery, Armed Forces Institute of Cardiology & National institute of Heart Diseases (AFIC/NIHD), Rawalpindi, from Sep 2011 to Jun 2017. Methodology: The study included all patients with diffuse CAD affecting the LAD, in whom conventional bypass grafting of the LAD was not possible. The long LAD reconstruction was avoided in those showing severe cal-cification of the atheroma or a long segmental stenosis with a lumen of less than 0.5mm on preoperative angio-graphy. Patients having severe multi-organ dysfunction, significant valvular pathology and predominantly non viable myocardium in the LAD territory were also excluded. Patients were followed up for mean period of 24 months for evaluation of early mortality and morbidity, angina status and survival. Results: Fifty-eight consecutive cases of LSR of the LAD were evaluated. The mean length of the LSR was 4.88 + 1.4cm (range 2.5 to 7.5cm). Seven (12.07%) had critical left main stem stenosis, 11 (18.97%) presented with unstable angina, 2 (3.45%) underwent emergency bypass graft surgery for post infarction angina, 17 (29.31%) had myocardial infarction (MI) in the past. There were 2 (3.45%) early deaths and 2 (3.45%) cases of non-fatal MI. At 24 months follow-up there were no late deaths; there was 1 (1.79%) case of late MI whereas 52 of the survivors (92.86%) had no angina; three (5.36%) had angina CCS I and 1 (1.79%) had angina CCS II. Conclusion: LSR of the diffusely diseased LAD with LIMA onlay patch grafting had acceptable operative risks and satisfactory results at 24 months in terms of mortality and relief from angina.